Nowe odczytanie „umowy fultońskiej” Winstona S. Churchilla (artykuł dyskusyjny) - Chmielewski, Paweł (Acta Universitatis Lodziensis. Folia Historica, 2001)
The author of the article argues with the generally accepted in historiography view, that the former Dritish Premier’s speech in Fulton in March 1946 (particularly his words about „the iron curtain”) was the beginning of the cold war. The documentation of monitoring led by Central Committe of the Polish Workers’ Party and its Foreign Section (available in the Archive of New Acts in Warsaw) allows to state that contemporary mass-media turned everybody’s attention to problem of Anglo-American allians and not to the need of inducing the Western world to the war with Soviet Union. In author’s opinion the Moscow authorities reactions and their propaganda ensured the „Fulton speech’s carriere”. The introducing article of „Pravda” of 11th March and the review with Stalin for the same newspaper two days later served that idea. There was the false interpretation of Churchill’s speech in both documents. In fact the Moscow propaganda steps started the period of tensions in international relation, characteristic for so called „cold war”.